Aldosterone infusion into the 4th ventricle produces sodium appetite with baroreflex attenuation independent of renal or blood pressure changes - Gasparini, S. [UNESP] (2018)
Aldosterone infusion into the 4th ventricle (4th V), upstream the nucleus of the solitary tract (NTS), produces strong 0.3 M NaCl intake. In the present study, we investigated whether aldosterone infusion into the 4th V activates HSD2 neurons, changes renal excretion, or alters blood pressure and cardiovascular reflexes. Chronic infusion of aldosterone (100 ng/h) into the 4th V increased daily 0.3 M NaCl intake (up to 44 ± 10, vs. vehicle: 5.6 ± 3.4 ml/24 h) and also c-Fos expression in HSD2 neurons in the NTS and in non-HSD2 neurons in the NTS. Natriuresis, diuresis and positive sodium balance were present in rats that ingested 0.3 M NaCl, however, renal excretion was not modified by 4th V aldosterone in rats that had no access to NaCl. 4th V aldosterone also reduced baroreflex sensitivity (−2.8 ± 0.5, vs. vehicle: −5.1 ± 0.9 bpm/mmHg) in animals that had sodium available, without changing blood pressure. The results suggest that sodium intake induced by aldosterone infused into the 4th V is associated with activation of NTS neurons, among them the HSD2 neurons. Aldosterone infused into the 4th V in association with sodium intake also impairs baroreflex sensitivity, without changing arterial pressure.